2020
DOI: 10.1016/j.isci.2020.101652
|View full text |Cite
|
Sign up to set email alerts
|

Two Homogametic Genotypes – One Crayfish: On the Consequences of Intersexuality

Abstract: Summary In the Australian redclaw crayfish, Cherax quadricarinatus (WZ/ZZ system), intersexuals, although exhibiting both male and female gonopores, are functional males bearing a female genotype (WZ males). Therefore, the occurrence of the unusual homogametic WW females in nature is plausible. We developed W/Z genomic sex markers and used them to investigate the genotypic structure of experimental and native C. quadricarinatus populations in Australia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…The sex chromosome of female giant freshwater prawn is heterogametic (Justo et al, 1991), with the chromosome code was WZ (Malecha et al, 1992). Furthermore, some of the previous studies has confirmed that there are other species with sex chromosome of WZ/ ZZ, i.e., crayfish and white shrimp (Guo et al, 2019;Levy et al, 2020). Levy et al (2020) stated that the chromosome system of WZ/ ZZ is commonly found in macruran decapoda crustacea (crayfish and lobster).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The sex chromosome of female giant freshwater prawn is heterogametic (Justo et al, 1991), with the chromosome code was WZ (Malecha et al, 1992). Furthermore, some of the previous studies has confirmed that there are other species with sex chromosome of WZ/ ZZ, i.e., crayfish and white shrimp (Guo et al, 2019;Levy et al, 2020). Levy et al (2020) stated that the chromosome system of WZ/ ZZ is commonly found in macruran decapoda crustacea (crayfish and lobster).…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, some of the previous studies has confirmed that there are other species with sex chromosome of WZ/ ZZ, i.e., crayfish and white shrimp (Guo et al, 2019;Levy et al, 2020). Levy et al (2020) stated that the chromosome system of WZ/ ZZ is commonly found in macruran decapoda crustacea (crayfish and lobster). However, until now, there is no identification report about sex chromosome mating of giant freshwater prawn from karyotyping process.…”
Section: Introductionmentioning
confidence: 94%
“…To find the sequence of the IAG mRNA in H. inermis (Hi-IAG), we aligned the IAG sequence from P. platyceros [Pnp-IAG; GenBank accession number: KX619617.1 (Levy et al, 2020a)] to the H. inermis body transcriptome generated in this study. From the IAG sequences that are available for dozens of decapod species, with different reproductive strategies and from various clades within the Crustacea (Levy and Sagi, 2020), Pnp-IAG was chosen for alignment due to the similar protandric nature of P. platyceros and H. inermis and their close evolutionary relationship (Wolfe et al, 2019;Levy et al, 2020c). After finding the Hi-IAG mRNA transcript in the body transcriptome of H. inermis, the predicted structure of the protein was inferred from its deduced amino acid sequence.…”
Section: Characterizing the Ag And Iag In H Inermismentioning
confidence: 99%
“…Important examples of sexual plasticity may be found among the crustaceans (Pandian, 2016), an ancient highly diverse group of animals in which a variety of reproductive strategies are represented, including gonochorism (separate sexes) (Juchault, 1999), intersexuality (combination of male and female features within a gonochoristic species) (Goldschmidt, 1938;Reinboth, 1975;Sagi et al, 1996;Abdel-Moneim et al, 2015;Levy et al, 2020c), asexual reproduction (e.g., parthenogenesis) (Scholtz et al, 2003;Martin et al, 2007), and different types of hermaphroditism (Levy et al, 2018;Benvenuto and Weeks, 2020). The last of these strategies constitutes a means of reproduction in which a particular individual bears both ovarian and testicular tissues [ovotestis (Hoffman, 1972;Stentiford, 2012)] and produces gametes of both sexes (Benvenuto and Weeks, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation